Pytanie o sens życia - Karol Bujnowski (Studia Ecologiae et Bioethicae)
Nowadays more often people are asking about the meaning of life. It is a fundamental question that every human being faces. Man is asking whether life is worth living, what to do to make our life meaningful? A human being, among many needs, has the need for discovering the sense of life, the need comes from the very core of human existence as placed in time and connected with the phenomenon of passing away. Discovering the sense of life leads to the experience of happiness, joy, and to inner life lived much more to the full. Showing the meaning of life and helping to find that meaning are very important functions of religion. Due to it, a man is able to live one’s life, ambitions, goals, joyful moments as well as his or her suffering in the light of deeper understanding. Religion is the one that can often bring the richest and deepest answers to the question of the two meanings: the meaning of life and the world.